2014
DOI: 10.1038/ijo.2014.209
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity and overnutrition increase oxidative stress in male rat offspring reproductive system and decrease fertility

Abstract: We conclude that MO during pregnancy and lactation increases F(1) testicular and sperm OS leading to premature aging of reproductive capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 60 publications
3
60
0
3
Order By: Relevance
“…67 a,b WM, Flard141PPPFAT, BWRodríguez-González G.L. 2015 a,b 68 WMlard141YA, AFAT, BWZambrano E. 69 WMlard141YAFAT, BW, LEP, GLU, INSSantos M. 70 WMlard141AFAT, BWZhang X. 71 SDMlard42YATGPage K.C.…”
Section: Resultsunclassified
“…67 a,b WM, Flard141PPPFAT, BWRodríguez-González G.L. 2015 a,b 68 WMlard141YA, AFAT, BWZambrano E. 69 WMlard141YAFAT, BW, LEP, GLU, INSSantos M. 70 WMlard141AFAT, BWZhang X. 71 SDMlard42YATGPage K.C.…”
Section: Resultsunclassified
“…So far, many different maternal programming factors have been discovered (for example over- or undernutrition [33-35], lack of micronutrients [36, 37], and stress during pregnancy [38-40]). However, more recent studies showed that also paternal exposure to adverse environmental conditions can act on the offspring’s phenotype in terms of fetal programming and influence later life disease risk [11, 28].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of ROS in beta-cell pathology is supported by the observation that 8-hydroxy-2′-deoxyguanosine (8-OHdG), an oxidative stress marker, is elevated in beta cells from diabetic Goto-Kakizaki (GK) rats (Ihara et al 1999) and that the insulin (Matsuoka et al 1997) and glucokinase (Kajimoto et al 1999) promoters are sensitive to glycation and the presence of ROS such as superoxide, hydrogen peroxide, nitric oxide and hydroxyl radicals. We have previously reported that oxidative stress has a deleterious effect on MO offspring testes as demonstrated by decreased fertility and numbers of spermatogonia and spermatocytes (Rodríguez-González et al 2015). Therefore, it is likely that in this study using the same experimental model, other organs are subject to oxidative stress and their functions could be jeopardized.…”
Section: :1mentioning
confidence: 88%